2018
DOI: 10.1029/2018jb015467
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Seismic Velocity Structure at the Junction of Kuril‐Northeastern Japan Arcs on Active Shallow Seismicity and Deep Low‐Frequency Earthquakes

Abstract: We estimate the velocity structures of P (Vp) and S waves (Vs) in southern Hokkaido, Japan, where a large number of crustal low‐frequency earthquakes (LFEs) have occurred. To investigate the relationship between structure and crustal seismicity, we compare the obtained velocity heterogeneity between the crustal LFE regions, which are characterized by active volcanoes, Quaternary volcanoes, and seismic swarms. The tomographic results show that low‐velocity zones (LVZs) with high Vp/Vs are located around the Moh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…These two low‐velocity zones roughly correspond to the depths of DLF earthquakes. Furthermore, the observations are consistent with the idea that DLF earthquakes occur in or around low‐velocity zones in many volcanoes (Hasegawa et al, ; Nakajima, ; Shiina et al, ). We may interpret that hypocenters of DLF earthquakes at Kirishima volcanoes may be concentrated at many small sources such as small magma reservoirs located in or around the magma sills in the low‐velocity zones (Figure ).…”
Section: Discussionsupporting
confidence: 87%
“…These two low‐velocity zones roughly correspond to the depths of DLF earthquakes. Furthermore, the observations are consistent with the idea that DLF earthquakes occur in or around low‐velocity zones in many volcanoes (Hasegawa et al, ; Nakajima, ; Shiina et al, ). We may interpret that hypocenters of DLF earthquakes at Kirishima volcanoes may be concentrated at many small sources such as small magma reservoirs located in or around the magma sills in the low‐velocity zones (Figure ).…”
Section: Discussionsupporting
confidence: 87%
“…The velocity of the S wave (V s ) was calculated at each depth as V p /1.73 with the assumption that the V p /V s ratio is 1.73. Recently several authors presented a 3-D tomographic model of V p and V s in this region (Katsumata et al 2006;Yoshida et al 2007;Kita et al 2012;Shiina et al 2018); thus, we assumed a 3-D velocity structure as shown in Additional file 1. The study area was divided into grids every 10 km in both the longitude and latitude directions on each plane at depths of 0, 5, 10, 22.5, 35, and 50 km.…”
Section: Analysesmentioning
confidence: 99%
“…The study area was divided into grids every 10 km in both the longitude and latitude directions on each plane at depths of 0, 5, 10, 22.5, 35, and 50 km. Values of V p and the V p /V s ratio at depths shallower than 10 km were based on Yoshida et al (2007), and those at depths equal to and deeper than 10 km were based on Shiina et al (2018).…”
Section: Analysesmentioning
confidence: 99%
“…Although validities of estimated Qs would be declined, these low-Qs areas beneath the volcanoes seem to extend towards the backarc region with depths. It would represent the upwelling flow in the mantle wedge which has been retrieved as low-velocity (e.g., Nakajima et al 2001;Kita et al 2014;Shiina et al 2018) and high-attenuation (Nakamura and Uetake 2004;Takahashi 2012;Nakajima et al 2013;Liu et al 2014) anomalies in P and S waves in the Hokkaido and the Tohoku district, Japan. At the forearc side from the volcanoes, the high-Qs zones are widely estimated at the depths of 30-40 km or deeper.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that S-wave attenuation in the Pacific slab and mantle wedge beneath the forearc region tend to be weak. It is known that attenuation effects can be modeled by the scattering attenuation and the intrinsic absorption (e.g., Hoshiba 1993; Takahashi et al 2009;Sato et al 2012). Carcolé and Sato (2010) mentioned characteristics in the two types of Qs using the multiple lapse time window analysis.…”
Section: Resultsmentioning
confidence: 99%